DUKUN JALUR DESA SAIK, KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Andini Venydhea; Mita Rosaliza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The purpose of this study namely: (1) to find out the History of Line Shamans in Saik Village (2) to find out how the Ritual Treatment Procession of the Line (3) is to describe How to Trust Shaman Lane in Saik Village, Kuantan Mudik District, Kuantan Singingi District, Riau Province. As for the informants, the Shaman in Saik Village is considered to know about the Path Ritual and in depth. This research method is qualitative by using the theory of Sacred Durheim and Profane Theories, Carl Gustav Jung's Archetype Theory and Ferdinand de Saussure's symbolic theory.The Kuantan Singingi community still believes in the existence of fine creatures that inhabit a place or object that is quite old. One example is the wood of the Track, the Path itself is made of wood that has been aged for hundreds of years and comes from the jungle in the wood. This wood can only be taken by people who understand about Subtle Creatures, namely Jalur Shaman. The equipment used and the track assistants in the process of the Jalur Shaman Rituals contain symbolic meaning, in the process the Jalur Shaman rituals are carried out by finding a good day of breaking to release the path to the Pacu jalur arena in order to get good draws, lime that has been incantated or prayed for and prayed for and kemeyan to call the Jalur ghost used in the Jalur Shaman Ritual as an effort Jalur Shaman Village Saik avoid attacks from Jalur Shaman opponents who try to harm the Jalur ghost, Jalur, and Pacu, in addition to chanting spells or prayers asking to be protected during the match the runway is aimed at Allah SWT, the mantra is also recited for the jalur ghost to help in Pacu Jalur competition. Keywords: jalur Shaman, Sacral, Ritual